THEORETICAL ASPECTS OF FORMATION OF HYGIENIC COMPETENCE IN STUDENTS OF MEDICAL EDUCATIONAL INSTITUTIONS (International journal of artificial intelligence, 2024)
The article examines the theoretical aspects of the formation of hygienic competence among students of medical educational institutions, pedagogical mechanisms and technological foundations of development. The pedagogical need for developing hygienic competence among students of medical educational institutions is also analyzed.